A comparison of attitudes towards immigrants from the perspective of the political party vote. Issue 3 (March 2023) - Indelicato, Alessandro; Martín, Juan Carlos; Scuderi, Raffaele
Abstract: Many reasons have shaped immigration into the EU over the past decade. Since then, attitudes towards immigration have not only gained public attention but have also shaped political debate and discourse in recent regional, national, and EU elections. The global financial crisis of 2008 increased the importance of migration in the social welfare upheaval in most Member States. Anti-immigrant sentiment and rhetoric became part of the narrative of some political parties during the campaign, and media coverage catalysed these social attitudes. The study used the 2013 International Social Survey Project (ISSP) dataset of six countries (namely Belgium, Germany, Spain, France, the UK, and Portugal) to see if the political party vote might have affected the attitude toward immigrants. The study extends other previous studies and presents new evidence on an under-researched topic. Results show that the left party voters are more open toward immigrants than the right party voters and that the green party voters show the most positive attitudes towards immigrants.